2014
DOI: 10.1002/oby.20679
|View full text |Cite
|
Sign up to set email alerts
|

Human adipocyte extracellular vesicles in reciprocal signaling between adipocytes and macrophages

Abstract: Objective: Extracellular vesicles (EVs) released by human adipocytes or adipose tissue (AT)-explants play a role in the paracrine interaction between adipocytes and macrophages, a key mechanism in AT inflammation, leading to metabolic complications like insulin resistance (IR) were determined. Methods: EVs released from in vitro differentiated adipocytes and AT-explants ex vivo were characterized by electron microscopy, Western blot, multiplex adipokine-profiling, and quantified by flow cytometry. Primary mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
155
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 42 publications
(60 reference statements)
9
155
1
5
Order By: Relevance
“…Once secreted, the majority of aP2 is detectable in the free form in circulation, but a small fraction persists in vesicles (data not shown). The vesicles bearing aP2 resemble exosomes in terms of size and marker expression, in agreement with previous reports ( 57 ). Our analysis of the density of the aP2-containing particles showed that they are at the high end of the density range reported for exosomes (1.19-1.21 g/ml) ( 58 ).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…Once secreted, the majority of aP2 is detectable in the free form in circulation, but a small fraction persists in vesicles (data not shown). The vesicles bearing aP2 resemble exosomes in terms of size and marker expression, in agreement with previous reports ( 57 ). Our analysis of the density of the aP2-containing particles showed that they are at the high end of the density range reported for exosomes (1.19-1.21 g/ml) ( 58 ).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…Exosomes isolated from adipose tissue mediated adipose tissue inflammation in a murine model [19]. Exosomes secreted by differentiated human adipocytes and human adipose tissue explants had immunomodulatory effects on macrophages, and exosome-stimulated macrophages induced insulin resistance in adipocytes [20]. However, no data are available on the signalling molecules carried by exosomes during communication between adipocytes and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Mouse visceral adipose tissue EVs mediate activation of macrophage-induced insulin resistance. 10 Cultures of murine pre-adipocytes have also been shown to release EVs and these EVs stimulate fatty acid-oxidation dependent migration of melanoma cells.…”
Section: Introductionmentioning
confidence: 99%